Indications and algorithm of treatments in adult spinal deformity. Issue 6 (December 2021) - Gandham, Surya; Samy, David; Annis, Prokopis
Abstract: The most common cause of spinal deformity in adults is iatrogenic flatback and degenerative scoliosis. With an aging population, complex disorders of the spine will become more prevalent and will necessitate correct assessment and management by specialists. Physical examination focusses on gait, posture and compensatory mechanisms. Specific radiological parameters are integrated with risk stratification indices to establish an appropriate treatment strategy. This paper outlines the steps needed to assess and plan appropriate treatment for adult spinal deformity.